Pengaruh Search Engine Marketing, Social Media Marketing, Digital Presence, Dan Customer Engagement Terhadap Customer Loyalty Melalui Brand Image Dan Trust Sebagai Mediasi: Studi Pada Pengguna Gojek Di Kota Semarang - Theo Benaya Saragih; Kardison Lumban Batu (Diponegoro Journal of Management, 2026)
This study aims to analyze the influence of search engine marketing, social media marketing, digital presence, and customer engagement on brand image, as well as their implications for trust and customer loyalty. This research employs a quantitative approach using Structural Equation Modeling (SEM) with AMOS version 24. Data were collected through questionnaires distributed to 100 respondents who are users of Gojek in Semarang City. The results indicate that customer engagement has the most dominant positive effect on brand image, followed by social media marketing, which also shows a significant positive influence. Meanwhile, digital presence has a significant negative effect, and search engine marketing does not have a significant effect on brand image. Furthermore, brand image has a positive and significant influence on both trust and customer loyalty, with trust emerging as the strongest determinant of customer loyalty. The model fit evaluation shows that most goodness-of-fit indices, such as RMSEA, CFI, and TLI, meet the recommended criteria, indicating that the model is acceptable. This study highlights that customer engagement and trust are key factors in building customer loyalty, rather than merely increasing digital exposure.